EXPLORING THE LITERATURE ON CONCEPTS OF TEACHER LEADERSHIP AND TEACHER-LEADER: IS THERE A DIFFERENCE? - Jurgilė, Vaida; Ponomarenko, Tetiana; Kaminskienė, Lina; Žydžiūnaitė, Vilma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of the current paper is to explore the concepts of “teacher leadership” and “teacher-leader”. The current article highlights and compares the usage of the two concepts, explores the new perspectives for determination of teacher leadership within school environment. It draws from literature on teacher leadership and on-the-job leadership development to explore insights and issues on teacher leadership development, and it presents cases for theoretical determination of both concepts. The concept analysis method was implemented in order to collect the recent literature and explore the concepts of “teacher leadership” and “teacher-leader”. The novelty of the current research is the definition of peculiarities in usage of both terms. The results indicate that the concept of teacher leadership is regarded as a process and activity, while the concept of teacher-leader is mostly regarded as a component of teacher’s professional identity. The article concludes with implications for further theoretical research on teacher leadership.